Technical and tactical readiness model characteristics in wrestling - Yuriy Tropin; Anton Chuev (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to develop model characteristics of technical and tactical preparedness of highly qualified wrestlers. Material & Methods: analysis of scientific and methodological information, generalization of best practical experience, pedagogical observation, analysis of video materials of competitive activities of wrestlers, modeling, methods of mathematical statistics. The results of 75 collisions of highly skilled Greco-Roman wrestlers were analyzed and summarized. Results: identified the 10 main technical actions that are most often used by wrestlers. Based on the analysis of competitive activity developed model characteristics of technical and tactical training of highly skilled wrestlers. Conclusion: analysis and models presented were the basis for the development of evaluation criteria and predicting the level of technical and tactical preparedness.